Semi-refined carrageenan induces eryptosis in a Ca2+-dependent manner - Anton Tkachenko; Volodymyr Prokopiuk; Anatolii Onishchenko (National Scientific Medical Center, 2022)
Background: Semi-refined carrageenan (food additive E407a) is a widely used thickener, which has been reported to exert toxic and pro-inflammatory effects. In particular, there is accumulating evidence that it induces eryptosis, i.e. a programmed cell death of eryptocytes, via ROS-mediated pathways. However, the role of Ca2+-dependent mechanisms in E407a-induced eryptosis is not elucidated. Material and methods: Semi-refined carrageenan at concentrations of 0 mg/ml, 1 mg/ml, 5 mg/ml and 10 mg/ml was incubated with blood of intact female WAG rats (n=9) for 24 h in RPMI and fetal bovine serum. After 24 h, the samples were used to obtain erythrocyte suspensions. The obtained suspensions were stained with a Ca2+-sensitive FLUO4 AM probe (30 min, 2.5 µM). The fluorescence of FLUO4 in erythrocytes was detected by a BD FACSCanto II flow cytometer. Results: The intracellular Ca2+ levels are proportional to the fluorescence of FLUO4. The mean fluorescence intensities (MFI) were compared. Low levels (1 mg/ml) of E407a had no impact on Ca2+ concentrations in erythrocytes (p>0.05). On the contrary, high concentrations (5 mg/ml and 10 mg/ml) of this food additive promoted an increase in the intracellular Ca2+ levels. The MFI values were 2.3- and 2.5-fold higher, respectively (p<0.0001). In addition, the exposure to E407a at concentrations of 5 mg/ml and 10 mg/ml (p<0.0001) increased the percentage of cells with high FLUO4 fluorescence. Conclusion: Food additive E407a induces eryptosis in a Ca2+-dependent manner.